Effect of freezing conservation time on loquat (Eriobotrya japonica) pollen germination - Beltrán, Roberto; Cebrián, Nuria; Zornoza, Carlos; Garmendia, Alfonso; Merle, Hugo B. (Spanish Journal of Agricultural Research, 2020)
Aim of study: Several studies point out that storage at -20 ºC is a suitable method for preserving pollen of many species in the long term. Part of those studies indicate the total storage time at which these conditions are optimal. However, we have found a lack of information about the freezing time conditions and incubation temperature of loquat pollen. The main objective of this study was to evaluate the effect of the -20 ºC conservation temperature on loquat  (Eriobotrya japonica (Thunb.) Lindl.) pollen.Area of study: The study was conducted in Montserrat (Valencia, Spain).Material and methods: Loquat flowers were collected in November 2017 and stored at -20 ºC for three time periods: 4 (T1), 6 (T2) and 8 (T3) months. Subsequently, pollen grains were incubated at different temperatures for 72 h. We analyzed (i) the effect of freezing conservation time; (ii) the effect of incubation temperature on germination; (iii) the interaction between these two factors.Main results: T1 showed higher germination percentage and tube length values (mean and maximum) than T2 and T3. The highest germination percentage (52.77%) was detected for T1 at an incubation temperature of 25 ºC. The interaction between freezing time and incubation temperature showed more consistent results for T1 than for T2 and T3.Research highlights: This suggests that storing at -20 ºC for more than 4 months affects pollen grain and reduces germination and pollen growth. Therefore, -20 ºC loquat pollen storage should not exceed 4 months.